1993
DOI: 10.2337/diab.42.10.1536
|View full text |Cite
|
Sign up to set email alerts
|

Availability of Type II Diabetic Families for Detection of Diabetes Susceptibility Genes

Abstract: Type II diabetes is a familial disorder, as evidenced by the increased prevalence in monozygotic cotwins and first-degree relatives of affected subjects; however, its genetic etiology is largely unknown. Well-characterized pedigrees are an essential resource for the study of susceptibility genes for type II diabetes. This study describes a 5-yr search for type II diabetic families in Oxfordshire, U.K. We interviewed 950 type II diabetic subjects concerning the availability of first-degree relatives; 127 Caucas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
1

Year Published

1994
1994
2005
2005

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 21 publications
0
13
1
Order By: Relevance
“…48, DECEMBER 1999 1 Potential availability of trios (diabetic proband with two living parents) and affected sibling pairs in a population-based questionnaire survey of 5,809 diabetic subjects (>99% U.K. C a u c a s i a n ) Treatment category Type 2 Type 1 A l l I n s u l i n O H A D i e t 24.2%, P < 0.0001) and were more obese than the sibling-pair probands (BMI 32.0 vs. 29.0 k g / m 2 , P < 0.0001; not available for population survey). In the trios in which parental status could be directly tested, no maternal excess was seen, as reported in the two other series in which both parents were available for testing (6,7). In contrast, our reported data in the sibling pairs and population series showed an excess of maternal diabetes, in keeping with other studies that used reported data (8).…”
contrasting
confidence: 61%
“…48, DECEMBER 1999 1 Potential availability of trios (diabetic proband with two living parents) and affected sibling pairs in a population-based questionnaire survey of 5,809 diabetic subjects (>99% U.K. C a u c a s i a n ) Treatment category Type 2 Type 1 A l l I n s u l i n O H A D i e t 24.2%, P < 0.0001) and were more obese than the sibling-pair probands (BMI 32.0 vs. 29.0 k g / m 2 , P < 0.0001; not available for population survey). In the trios in which parental status could be directly tested, no maternal excess was seen, as reported in the two other series in which both parents were available for testing (6,7). In contrast, our reported data in the sibling pairs and population series showed an excess of maternal diabetes, in keeping with other studies that used reported data (8).…”
contrasting
confidence: 61%
“…In a study of the ascertainment of suitable pedigrees from 950 known diabetic patients in Oxfordshire, only 127 (13%) families were available for study [8]. The strategy investigated in this study was based on the identification of probands with a history of gestational diabetes who, on retesting, had evidence of IGT or NIDDM, with subsequent testing of their parents.…”
Section: Discussionmentioning
confidence: 99%
“…Of the 35 potential probands, 40 % of patients and parents were available and willing to be studied as a family, representing 23 % of those with fasting hyperglycaemia. This is a larger yield than that from known diabetic patients in the Oxfordshire study [8], and provides a complementary strategy for the collection of pedigree data suitable for genetic studies. As one might expect that those with a diabetic parent would be more likely to volunteer for the study, this would counteract any potential bias from not being able to study families in which a parent had died from a diabetes-related cause.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Probands were aged 35 years or older at the time of diagnosis of diabetes. Families with three or more siblings and a quarter of families with two siblings living within the study area were approached to establish whether they were willing to be recruited to the program [13]. The proband assessed the willingness of their siblings to be approached as potential study volunteers, and the research team then contacted those interested.…”
Section: Participants and Methodsmentioning
confidence: 99%